PASSARE AL BIM 10 regole per avere successo - Marco Parisi (GEOmedia, 2015)
Many companies are beginning to use BIM software or have already started but have stalled. We see 10 rules to follow to ensure that the transition from CAD to BIM of a project department can be successful. Of all the activities related to the life of a building, embraced by BIM methodology, we focus today on those related to the design. Proceed by steps, to dedicate a small team, well-chosen and motivated, understand right away the new workflow, are some of the tips of the article. These tips do not cover all the things you need to know to start a BIM process but I believe they can help to avoid the most common mistakes that you make at the beginning of the journey. We use the BIM process because it gives us benefits. Because it saves time and makes us produce work of the highest quality. If we do not reach this convenience means that in our process BIM's about to change.